The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fepid.2022.1011938
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletions and high diversity of Plasmodium falciparum histidine-rich proteins 2 and 3 genes in parasite populations in Ghana

Abstract: Rapid diagnostic tests (RDTs) are used to diagnose malaria in Ghana and other malaria endemic countries. Plasmodium falciparum histidine-rich protein 2 (PFHRP2) based RDTs are widely used, however the occurrence of deletions of the pfhrp2 gene in some parasites have resulted in false negative test results. Monoclonal antibodies of PFHRP2 cross reacts with PFHRP3 because they share structural similarities and this complements the detection of the parasites by RDT. These two genes were investigated in Ghanaian P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Finally, some of the malaria parasites have mutated their hrp2 genes, making them unable to synthesis the HRP2 proteins [ 40 ] and parasites in Ghana are not exception. In a study published in 2022 by Duah-Quashie et al [ 41 ], it was revealed that 30.7% and 17.2% of malaria parasites had their pfhrp2 and pfhrp3 genes, respectively deleted. It is for these reasons that mRDTs that detect both PfHRP2 and pLDH is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some of the malaria parasites have mutated their hrp2 genes, making them unable to synthesis the HRP2 proteins [ 40 ] and parasites in Ghana are not exception. In a study published in 2022 by Duah-Quashie et al [ 41 ], it was revealed that 30.7% and 17.2% of malaria parasites had their pfhrp2 and pfhrp3 genes, respectively deleted. It is for these reasons that mRDTs that detect both PfHRP2 and pLDH is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…There are geographical differences in the prevalence of deletions in areas where malaria is endemic. Studies carried out in Ghana have not observed any deletions in the middle belt of Ghana [ 32 ], whereas deletions have been observed in Ghanaian isolates in the coastal part of Ghana [ 35 ], with worrying proportions of parasites with a double deletion in 30.7 and 17.2% of isolates for the pfhrp2 and pfhrp3 genes, respectively [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, deletions in the hrp2 and hrp3 genes will lead to false-negative RDT results, even in patients with high parasite density infections [4,9]. These deletions have been observed in various countries, in particular in east Aftica [10][11][12], but also at low frequencies in Ghana [13].…”
Section: Introductionmentioning
confidence: 99%